Rhizosphere allocation by canopy-forming species dominates soil CO2 efflux in a subarctic landscape. - Parker, TC; Clemmensen, KE; Friggens, NL; Hartley, IP; Johnson, D; Lindahl, BD; Olofsson, J; Siewert, MB; Street, LE; Subke, J-A; Wookey, PA (New Phytologist, 2020)
This is the author accepted manuscript. The final version is available from Wiley via the DOI in this record In arctic ecosystems, climate change has increased plant productivity. As arctic carbon (C) stocks are predominantly located below ground, the effects of greater plant productivity on soil C storage will significantly determine the net sink/source potential of these ecosystems, but vegetation controls on soil CO2 efflux remain poorly resolved. To identify the role of canopy-forming species in below-ground C dynamics, we conducted a girdling experiment with plots distributed across 1 km2 of treeline birch (Betula pubescens) forest and willow (Salix lapponum) patches in northern Sweden and quantified the contribution of canopy vegetation to soil CO2 fluxes and below-ground productivity. Girdling birches reduced total soil CO2 efflux in the peak growing season by 53% -double the expected amount, given that trees contribute only half of the total leaf area in the forest. Root and mycorrhizal mycelial production also decreased substantially. At peak season, willow shrubs contributed 38% to soil CO2 efflux in their patches. Our findings indicate that C, recently fixed by trees and tall shrubs, makes a substantial contribution to soil respiration. It is critically important that these processes are taken into consideration in the context of a greening arctic since productivity and ecosystem C sequestration are not synonymous. Natural Environment Research Council (NERC)